Analisis Strategi Relationship Marketing dalam Membangun Jaringan Bisnis pada Groei Coffe di Sukapura Kabupaten Bandung - Resya Dwi Marselina; M. Rizal Septiadi; Salman Noviar Natanagara; Vian Ginanzar; M. Zaqi Abdul Wahab (Jurnal Manajemen Bisnis Digital Terkini, 2026)
The increasing competition in the coffee shop industry in Bandung requires businesses to adopt marketing strategies that emphasize long-term relationships with customers. This study aims to analyze the implementation of relationship marketing strategies in building business networks at Groei Coffee, a community-based café located in Sukapura, Bandung Regency. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings indicate that relationship marketing at Groei Coffee is implemented through consistent product quality, two-way communication with customers, personalized services, and collaboration with campus communities and strategic partners. These strategies have proven effective in enhancing customer loyalty, expanding business networks, and strengthening the café’s competitive position in the food and beverage industry. However, several challenges were identified, including limited resources, price sensitivity among student customers, and dynamic consumer preferences. Therefore, an adaptive and sustainable approach is required to ensure that relationship marketing strategies provide long-term benefits for small and medium-sized enterprises (SMEs).